2013
DOI: 10.1530/eje-12-0714
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations of the calcium-sensing receptor gene affecting the same amino acid position lead to opposite phenotypes and reveal the importance of p.N802 on receptor activity

Abstract: Objective: Gain-of-function mutations of the calcium-sensing receptor (CASR) gene have been identified in patients with sporadic or familial autosomal dominant hypocalcemia (ADH). Inactivating mutations of the CASR gene cause familial hypocalciuric hypercalcemia (FHH). Here, we report two novel CASR mutations affecting the same amino acid (p.N802); one causes ADH and the other atypical FHH. Patients and methods: The first patient, an 11-year-old girl suffering from hypocalcemia, developed nephrocalcinosis when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Only two of 4 known CaSR mutants were sensitive to NPS-2143 either expressed alone or when co-expressed with wt-CaSR to approximate heterozygosity in patients. This resembles previous data from us and others showing that some but not all ADH CaSR mutants were sensitive to NPS-2143 [20] , [34] , [35] . Thus, amino alcohol derived calcilytics may not be the ideal drugs to treat disorders caused by activating CaSR mutations.…”
Section: Discussionsupporting
confidence: 91%
“…Only two of 4 known CaSR mutants were sensitive to NPS-2143 either expressed alone or when co-expressed with wt-CaSR to approximate heterozygosity in patients. This resembles previous data from us and others showing that some but not all ADH CaSR mutants were sensitive to NPS-2143 [20] , [34] , [35] . Thus, amino alcohol derived calcilytics may not be the ideal drugs to treat disorders caused by activating CaSR mutations.…”
Section: Discussionsupporting
confidence: 91%
“…NPS 2143 was used as it induces more prolonged elevations in circulating PTH concentrations than other calcilytic drugs ( 17 , 31 ) and has been shown to be safe and well tolerated in rodent studies ( 15 ). However, previous in vitro studies have indicated that NPS 2143 may not be a suitable therapy for all gain-of-function CaSR mutations ( 19 22 , 25 ). Indeed, ADH-associated CaSR mutations, such as Ala835Asp and Ala843Glu, which are located close to the Glu837 TMD residue that is critical for NPS 2143 binding (Supplemental Figure 1) ( 19 , 21 , 32 ), have been demonstrated to completely abrogate the action of NPS 2143, whereas ADH-associated TMD CaSR mutations located away from known NPS 2143 binding residues, such as Glu767Gln, Leu773Arg and Asn802Ile, may partially diminish the efficacy of this calcilytic compound (Supplemental Figure 1) ( 20 , 22 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prolonged exposure of cells expressing gain-of-function mutant CaSRs to calcilytic drugs may facilitate internalization of these allosteric modulators, which then bind and destabilize the conformation of nascent CaSRs, thus leading to enhanced proteasomal degradation of mutant receptors ( Figure 1 ) ( 7 , 8 ). However, some gain-of-function mutations located within the CaSR transmembrane domain (TMD), which is predicted to be the binding site for allosteric CaSR modulators ( 23 , 24 ), have been shown to impair the effectiveness of calcilytic drugs ( Supplemental Figure 1 ) ( 19 22 , 25 ). Moreover, it is unclear whether calcilytic drugs may improve the hypocalcemia of ADH1 while minimizing the risk of hypercalciuric renal disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NPS-2143 and its close relative ronacaleret are amino-alcohols, whereas ATF936 and AXT914 are quinazolinones. These different classes of calcilytics have partly different bindings sites (48) and data from four publications show that some but not all ADH CASR mutants were sensitive to NPS-2143 (108,111,112,113). In contrast all five ADH and all four BS5 mutants tested so far were sensitive to ATF936 and AXT914 (111).…”
Section: -27mentioning
confidence: 99%